The reality of using hybrid learning in the faculty of education for pure sciences from the teaching point of view - Anaya, Zahraa Hassan (Edelweiss Applied Science and Technology, 2024)
The study was aimed at identifying the reality of the use of hybrid education from the point of view of teachers at the Faculty of Education for Pure Sciences at Dhu Qar University. The study used the curriculum. The sample of the research was the teaching and number of the Faculty of Education for Pure Sciences at Dhu Qar University. (101) Teaching and teaching, the research tool was the hybrid learning questionnaire consisting of (40) A paragraph, applied to the sample in 2023, after some adjustments to it by extracting honesty and consistency, and after statistical analyses the results of the research showed: The most important was the presence of a (high) level of teaching staff at the Faculty of Education for Pure Sciences in the use of hybrid learning, and the study concluded a number of recommendations and proposals.